Analisis Penerapan Prinsip Dasar Animasi Dalam Animasi “Weathering With You” - Abyan Dhia Pratama (Peneliti.net, 2023)
Animation is a collection of moving images that form a sequence of frames, creating motion. Good animation can bring a story to life and leave a lasting impression on viewers. Therefore, Ollie Johnston and Frank Thomas, the individuals behind classic Disney animated films like Sleeping Beauty and Cinderella, created 12 fundamental principles of animation. This research aims to determine whether the Japanese animation titled